GOLDEN VISA GRANTING POLICY AS AN EFFORT TO INVESTMENT ATTRACTION IN INDONESIA - Fakhriza, Dandi (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2023)
ABSTRACT; The Government of the Republic of Indonesia issued Regulation of the Minister of Law and Human Rights (Permenkumham) Number 22 of 2023 concerning Visas and Residence Permits as well as Regulation of the Minister of Finance Number 82 of 2023 concerning Types and Tariffs for Types of Non-Tax State Revenue. The Minister of Law and Human Rights Regulation and the Minister of Finance Regulation function as regulations for granting golden visas to investors who wish to invest their capital in Indonesia. The approach method used is empirical juridical with research specifications that are descriptive analytical. The things studied are the policy of granting golden visas to foreign investors in Indonesia and the form of incentives for granting golden visas to foreign investors to invest in Indonesia. In the end, the researchers concluded that the golden visa imposed by the government on foreign investors was a temporary residence permit with a period of 5 (five) years for individual investors and a temporary residence permit with a period of 5 (five) years to 10 (ten) years for corporate investors, then get ease in entering and exiting Indonesia, and ease in not processing a limited residence permit in Indonesia.